Social Media Integration In Secondary Education In Pakistan (Journal of Education and Educational Development, 2020)
This paper investigates the adequacy of social media implementation in the context of secondary education in Pakistan and highlights the importance and necessity of social media in secondary education. This research has helped in understanding the pros and cons of social media implementation in classrooms and also facilitated in analyzing whether social media helps in student learning, classroom performances, competencies and academic grow. The qualitative study paradigm was used for this research. Six phenomenological interviews were conducted from secondary school teachers.In the light of the derived results. It was concluded that social media was an essential tool that could be used to make classrooms more engaging and ethnically diverse. Results suggested that teachers spent time implementing social media in their classrooms for academic purposes and teachers used these forums for self-education and to interact with like-minded people. Social media can serve the most momentous purposes in education system as today’s digitalized world is all about the Internet and technology, and hence it becomes compulsory for the educationist to understand the importance social networking